Development of physical intrusion detection system using Wi-Fi / ZigBee RF signals - Habaebi, Mohamed Hadi; Ali, Mahamat Mahamat; Hassan, M. M.; Shoib, M. S.; Zahrudin, A. A.; Kamarulzaman, A. A.; Wan Azhan, W. S.; Islam, Md. Rafiqul (Elsevier Ltd., 2015)
Wi-Fi is a wireless networking technology that enables computers and other devices to communicate using a RF signal enabling a lot of advanced applications to provide services. Nowadays, Wi-Fi signal coverage is almost a must in any office building or small office home office (SOHO) environment. Home and office networking concept involves the use of wireless sensors/Wi-Fi routers around the house to control and detect signals in the home-setting. In this project, however, RF signals from Wi-Fi NIC and ZigBee motes received signal strength indicators (RSSI) were used as a base feed to our system testbed to detect the human presence inside an indoor home/office environment. Then, a controller is used to switch ON/OFF appliances like air conditioning, lights …etc. The system testbed doubles as a reliable alarm for physical intrusion detection to secure an indoor perimeter as demonstrated in the paper. This simple, yet cheap, approach to home/office networking promises to save energy and cost in large numbers. It can also be used in many industrial settings including control and security applications.